Understanding Biology Pre-service Teachers’ Acceptance of PjBL e-logbook: An Application of the UTAUT Model at Universitas Jambi - Siburian, Jodion; Sanjaya, M. Erick; Tentia, Ine; Mataniari, Raissa; Sembiring, Dian Arisandy Eka Putra (Educational Leadership and Management Journal, 2025)
This study investigates factors influencing students’ acceptance and use of a Project-Based Learning (PjBL) e‑logbook in biology education at Universitas Jambi, using the Unified Theory of Acceptance and Use of Technology (UTAUT). The PjBL e‑logbook was implemented in core courses of the Biology Education Study Program to support structured documentation, monitoring, and reflection on project work. An explanatory survey design was employed with 133 undergraduate students in biology education who had used the e‑logbook for at least 4 weeks. Data were collected using a UTAUT-based questionnaire covering performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), behavioral intention (BI), and the PjBL e-logbook use behavior (UB). Partial least squares structural equation modeling (PLS‑SEM) was used to assess the measurement and structural models. The results show that PE (β = 0.38, p < .001), EE (β = 0.21, p = .018), and SI (β = 0.16, p = .049) significantly predict BI, whereas FC has a positive but non-significant effect on BI (β = 0.11, p = .148). Together, these UTAUT constructs explain 52% of the variance in BI. BI strongly predicts the PjBL e‑logbook use behavior (β = 0.56, p < .001), and FC also has a modest direct effect on UB (β = 0.19, p = .028), with the model explaining 39% of the variance in UB. The findings highlight the central role of perceived usefulness, ease of use, and social influences in promoting intention, and confirm the importance of both intention and facilitating conditions for actual e‑logbook use. Practical implications for designing and scaling PjBL e‑logbooks in teacher education at Universitas Jambi and similar institutions are discussed.